2018
DOI: 10.1038/s41390-018-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cholesterol levels and brain development in preterm newborns

Abstract: Objective:To assess whether postnatal plasma cholesterol levels are associated with microstructural and macrostrucural regional brain development in preterm newborns.Methods:Sixty preterm newborns (born 24-32 weeks gestational age) were assessed using MRI studies soon after birth and again at term-equivalent age. Blood samples were obtained within 7 days of each MRI scan to analyze for plasma cholesterol and lathosterol (a marker of endogenous cholesterol synthesis) levels. Outcomes were assessed at 3 years us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Besides, we can not exclude that systemic effect of atorvastatin on cholesterol synthesis may be influencing the atorvastatin-induced effects. One previous study has revealed that higher cholesterol is associated with impaired white matter development and worse motor outcomes in preterm newborns [ 67 ]. Puglielli et al [ 68 ] have found that increased cholesterol can lead to the development of Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we can not exclude that systemic effect of atorvastatin on cholesterol synthesis may be influencing the atorvastatin-induced effects. One previous study has revealed that higher cholesterol is associated with impaired white matter development and worse motor outcomes in preterm newborns [ 67 ]. Puglielli et al [ 68 ] have found that increased cholesterol can lead to the development of Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Lanosterol, the first sterol committed to cholesterol synthesis and, therefore, considered as a surrogate for cholesterol, is able to induce mild depolarization of mitochondria and promote autophagy and protect dopaminergic neurons from cell death in a model of Parkinson’s disease [ 17 ]. Higher plasma lathosterol, another marker of endogenous cholesterol synthesis, is associated with impaired white matter development and worse motor outcomes in preterm newborns [ 18 ]. Further upstream in the isoprenoid pathway, geranylgeraniol (GG) formed from farnesyl pyrophosphate (FPP) and geranylgeranyl-PP is found to be required for hippocampal long-term potentiation (LTP) and learning/memory [ 19 ].…”
Section: Cholesterol Biosynthesis and Accretion During Brain Developmentmentioning
confidence: 99%
“…In addition, a clinical study assessing the relationship between plasma cholesterol levels and brain development in 60 preterm infants showed that higher early endogenous cholesterol synthesis represented by higher lathosterol levels is associated with subcortical white matter edema and worse motor outcomes. Higher early blood cholesterol is associated with improved cerebellar volumes [ 18 ]. Although plasma cholesterol is separate from brain cholesterol, the issues in nutrition/metabolism, infections/immune system, the liver, or cardiovascular system that affect blood cholesterol may indirectly impact brain development in premature babies.…”
Section: Plasma Cholesterol and Brain Develop-ment In Preterm Newbornsmentioning
confidence: 99%
“…In this regard, short- and long-chain polyunsaturated fatty acids (PUFAs) as well as cholesterol are indispensable building blocks for myelin production ( Dimas et al, 2019 ; Hussain et al, 2019 ). Disturbance of cholesterol homeostasis following HI in neonatal brain was associated with worse subcortical white matter development ( Kamino et al, 2019 ; Marangon et al, 2020 ). To this end, an ongoing clinical trial is currently evaluating the effect of early nutritional supply in brain maturation and neonatal outcomes in preterm infants ( ClinicalTrials.gov NCT03555019) ( Chan et al, 2016 ; Wendel et al, 2021 ).…”
Section: Enhancing Oligodendrocytes Myelination As Therapeutic Strategies Against White Matter Injurymentioning
confidence: 99%